HUBUNGAN KECEPATAN LARI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA KELAS IV SDN 009 PARIT TERATAK AIR HITAM KECAMATAN BENAI - Yunus, Deril; Saripin, Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, based on the observation that the author did in SDN 009 Air Hitam, Parit Teratak Sentajo Raya subdistrict there are phenomena of which, is the low ability students, in the long jump, with a leap generated no more than 2 meters. The problem is apparently due to low speed run that owned the students, therefore the researchers aim to conduct research on the relationship speed to run with the results of the long jump. This type of research is correlational, meaning a statistical board, which can be used to compare the results of measurements of two different variables in order to determine the degree of association between these variables (Arikunto, 2006: 273). In this study serve as a speed variable